Do you feel safe here? The role of psychological safety in the relationship between transformational leadership and turnover intention amid COVID-19 Pandemic - Abu Elnasr E. Sobaih; Hassane Gharbi; Ahmed E. Abu Elnasr (Journal of Risk and Financial Management, 2022)
Despite their significant role in the performance of hotel industry, hotel workers are suffering from high rates of turnover, due to several reasons, particularly amid the COVID-19 pandemic. The pandemic has had numerous negative consequences on hotel workers, including their intention to leave the job or/and career. This study is an attempt to investigate the impact of transformational leadership on turnover intention amid COVID-19 and how psychological safety can intermediate this relationship. The study used a quantitative research approach via a pre-test instrument, self-distributed and collected from hotel workers at different regions in the Kingdom of Saudi Arabia (KSA). Valid responses from 1228 workers, analyzed through a structural equation modeling (SEM) of AMOS version 23, showed that transformational leadership has a significant negative impact on turnover intention as hypothesized. Nevertheless, it has a significant positive impact on psychological safety, whereas psychological safety has a significant negative impact on turnover intention. The most important finding of this study was the perfect mediating effect of psychological safety in the link between transformational leadership and workers' turnover intention. This finding confirms that psychological safety has the ability to change the above-mentioned link. In other words, the presence of psychological safety ensures negative turnover intention, even if transformational leadership practices do not exist. The findings have implications for scholars and practitioners, especially in tourism and hotel context, in relation to the role of psychological safety and transformational leadership in creating a sustainable working environment to maintain a lower turnover intention.
Keywords: 650; hotel industry; Kingdom of Saudi Arabia (KSA); psychological safety; social exchange theory; transformational leadership; turnover intention